Body height and age at menarche of girls from eastern Poland in the period of political transformation - Saczuk, Jerzy; Wasiluk, Agnieszka; Wilczewski, Adam (Anthropological Review, 2018)
Biological state of a group of people or particular individuals in various phases of ontogenesis should be treated as a positive health measure. The aim of the study was to assess the directions of changes in body height and age at menarche of girls from eastern Poland in the years 1986-2016. The data regarding 30784 students aged 10-16 living in towns and villages of the eastern parts of such regions as Podkarpackie, Lubelskie, Podlaskie, Warminsko-mazurskie and, to a slight extent, Mazowieckie were used in the study. Body height was measured and information concerning the place of living and age at menarche (yes-no) was gathered during interviews. Acceleration of body height and age at menarche was observed in girls from the east of Poland in the period of political transformation and after European Union (EU) accession, while the level of secular trends was connected with the pace of changes in the environment. Biological effects of the EU preservation of Polish agriculture and particular care of the eastern provinces of Poland reduced developmental differences between these provinces and other regions of Poland. Moreover, in the analysed period of three decades (1986-2016), the disappearance of differences in body height and age at menarche between the inhabitants of rural and urban areas was noted, which indicates larger positive socio-economic changes in the countryside. In turn, greater body height was noted in non-menstruating girls compared to their menstruating counterparts. However, in subsequent observations, smaller differences between these groups were observed. Biological state of a group of people or particular individuals in various phases of ontogenesis should be treated as a positive health measure. The aim of the study was to assess the directions of changes in body height and age at menarche of girls from eastern Poland in the years 1986-2016. The data regarding 30784 students aged 10-16 living in towns and villages of the eastern parts of such regions as Podkarpackie, Lubelskie, Podlaskie, Warminsko-mazurskie and, to a slight extent, Mazowieckie were used in the study. Body height was measured and information concerning the place of living and age at menarche (yes-no) was gathered during interviews. Acceleration of body height and age at menarche was observed in girls from the east of Poland in the period of political transformation and after European Union (EU) accession, while the level of secular trends was connected with the pace of changes in the environment. Biological effects of the EU preservation of Polish agriculture and particular care of the eastern provinces of Poland reduced developmental differences between these provinces and other regions of Poland. Moreover, in the analysed period of three decades (1986-2016), the disappearance of differences in body height and age at menarche between the inhabitants of rural and urban areas was noted, which indicates larger positive socio-economic changes in the countryside. In turn, greater body height was noted in non-menstruating girls compared to their menstruating counterparts. However, in subsequent observations, smaller differences between these groups were observed.